Organizational culture and innovation: a thematic analysis in Costa Rica's firms - Vargas Halabi, Tomás (2015)
This exploratory research linked the impressions of five Costa Rican companies managers interviewed, with the sub-dimensions and three dimensions of Denison Organizational Culture Survey (DOCS) culture traits: mission, involvement and adaptability; and their link with the innovation in their companies. It is based on a thematic analysis and a modification of the elaborative encoding of verbal expressions, given by Auerbach & Silverstein (2003), in order to obtain topics from the meanings of specific expressions of respondents, and link them to latent variables of DOCS model and the innovation. The verbal data processing was performed using the Atlas Ti 6 software. The results showed the importance of having a purpose and strategic direction to align efforts for the innovative activity in the company. This involves the capacity of the employees to have a customer focus skills, learn new skills and create change in the organization. While the above findings are consistent with literature on this subject, a contribution of this study points to the potential effect of adaptability and involvement on innovation, though, mediated by the cultural trait mission.